PHYSICAL AND CHEMICAL STABILITY STUDY OF LINIMENT AS ANALGESIC BASED ON RED GINGER ESSENTIAL OIL (ZINGIBER OFFICINALE VAR. RUBRUM) DURING STORAGE - Titi Agni Hutahaen; Atika Nirmala; Faradila Arifin Putri; Umi Muslihatun Nikmah (RADJA PUBLIKA, 2025)
Red ginger essential oil (Zingiber officinale var. Rubrum) has potential as a natural analgesic applied in liniment preparations. However, the physical and chemical stability of this preparation during storage needs to be evaluated to ensure its effectiveness and safety. Changes in pH, viscosity, homogeneity, and degradation of active compounds can affect the quality of the liniment over time. Therefore, this study aims to evaluate the physical and chemical stability of red ginger essential oil-based liniment under various storage conditions. The research methods include physical stability testing with organoleptic analysis (color, odor, clarity), pH, viscosity, and homogeneity. Chemical stability was analyzed using Gas Chromatography-Mass Spectrometry (GC-MS) to identify changes in the content of bioactive compounds. The liniment was stored under three conditions: room temperature (25°C), accelerated temperature (40°C), and cold temperature (4°C). The organoleptic test results showed a light yellow color with a characteristic red ginger odor. The pH test results for the liniment fell within the required pH range. The comfort test using the Visual Analogue Scale (VAS) yielded results interpreted as very comfortable. Physical stability tests at three different temperatures showed stable results. GCMS testing at 40°C showed degradation of zingiberene compounds by 30-35%, including βsesquiphellandrene, champene and alfa pinene. Therefore, proper storage is a critical factor in maintaining purity and pharmacological efficacy.